Архітектурно-інженерні аспекти реновації актового залу і навчального корпусу національного університету “львівська політехніка” - Яців, М. Б.; Нестерович, Е. А.; Yatsiv, M.; Nesterovich, E. (Видавництво Львівської політехніки, 2018)
Здійснено комплексний аналіз архітектурно-інженерних проблем функціонування наявного актового залу, встановлено найважливіші чинники формування світлового та акустичного дискомфорту приміщення, запропоновано варіанти оптимізації світлового та акустичного середовища залу, визначено методи та засоби гармонізації середовища залу із урахуванням проектів реновації.

Academic educational and laboratory building No.l was the first new building of Lviv Polytechnic University. However, at the beginning of 2000 the hall ran out of technical and technological capabilities as well as functional ones. Apart from academic, methodical, ideological events significant space in the hall was occupied by artistic ones, however during 60 % of time this biggest of university spaces was kept half empty. At the request of the Rector the head of the department of architectural environment design and its leading pedagogues decided to broaden functional palette of an existing hall. Extending theatrically- performing function was chosen as the main renovation vector and it would satisfy the needs of not only students but also citizens and city guests. The purpose of the renovation project - to develop architectural conception of renovating historical hall having secured using there a wide range of modern events and means of functional activity and having guaranteed aesthetic solution of its environment in accordance with the demands of the 2lst century and at the same time having preserved tectonics and vividness of that time when the project had emerged and construction had been conducted. Project of renovating assembly hall and improving its theatrically-performing function is conceptually connected with transforming space of the whole building taking into consideration existing and new functional premises. The study of the comfort of the assembly hall environment, after its architectural reconstruction, is the engineering context of the article. The influence of new planning parameters, replacement of technological equipment of the hall and materials of wall surface coatings on the nature of visual perception, features of arrangement of natural and artificial lighting systems is considered. Modernization of hall acoustic equipment was suggested in accordance with modern demands. Conclusion. Architectural, constructive, aesthetic and engineering-technological issues of renovation must be solved in a complex way, since introducing into the tectonic structure and room space of the new planning and subject-space elements and ignoring the requirements of the comfort of the environment of the hall can negatively affect the conditions of visibility, the nature of the visual perception, its illumination and acoustics.
Architectural-engineering aspects of the renovation of the assembly hallthe 1-st academic building of Lviv polytechnic national university
Keywords: реновація; сприйняття інтер’єру; природне освітлення; світловий дискомфорт; методи освітлення; акустика залів; реверберація; артикуляція; renovation; interior perception; lighting discomfort; lighting methods; acoustics of halls; reverb; articulation; 721.01 727; 534.3